Beneficiaries' perspectives on improved oral health and its mediators after Medicaid expansion in Michigan: a mixed methods study. (22nd March 2021) - Kieffer, Edith C.; Goold, Susan D.; Buchmueller, Tom; Nalliah, Romesh; Beathard, Erin; Kirch, Matthias A.; Solway, Erica; Tipirneni, Renuka; Clark, Sarah J.; Haggins, Adrianne N.; Patel, Minal R.; Ayanian, John Z.
Abstract: Objective: To investigate self‐reported improved oral health and its mediators, and job‐related outcomes, of Medicaid expansion beneficiaries in Michigan. Methods: This cross‐sectional mixed‐methods study of adult "Healthy Michigan Plan" (HMP) Medicaid expansion beneficiaries included qualitative interviews with a convenience sample of 67 beneficiaries enrolled for ≥6 months, a stratified random sample survey of 4, 090 beneficiaries enrolled for ≥12 months; and Medicaid claims data. We examined unadjusted associations between demographic variables and awareness of dental coverage, self‐reported dental care access, dental visits, and self‐reported oral health; and between improved oral health and job seeking and job performance. Multivariate analysis examined factors associated with self‐reported oral health improvement, adjusting for sociodemographic characteristics, prior health insurance, and having at least one dental visit claim. Results: Among surveyed beneficiaries, 60 percent received ≥1 dental visit and 40 percent reported improved oral health. Adjusted odds ratios (aOR) for improved oral health were higher for African‐American beneficiaries [aOR = 1.61; confidence interval (CI) = 1.28‐2.03] and those previously uninsured for ≥12 months (aOR = 1.96; CI = 1.58‐2.43). Beneficiaries reporting improved oral health were more likely to report improved job seeking (59.9 percent vs 51 percent; P = 0.04) and job performance (76.1 percent vs 65.0 percent; P < 0.001) due to HMP. Interviewees described previously unmet oral health needs, and treatments that improved oral health, functioning, appearance, confidence, and employability. Conclusion: Michigan's Medicaid expansion contributed to self‐reported improved oral health, which was associated with improved job outcomes. Policymakers should consider the importance of Medicaid dental coverage in reducing oral health disparities and improving the health and socioeconomic well‐being of low‐income adults and communities when considering this optional benefit.